2010
DOI: 10.1007/s12265-010-9189-3
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Induced by Ischemic Preconditioning is Essential for Cardioprotection

Abstract: Based on growing evidence linking autophagy to preconditioning, we tested the hypothesis that autophagy is necessary for cardioprotection conferred by ischemic preconditioning (IPC). We induced IPC with three cycles of 5 min regional ischemia alternating with 5 min reperfusion and assessed the induction of autophagy in mCherry-LC3 transgenic mice by imaging of fluorescent autophagosomes in cryosections. We found a rapid and significant increase in the number of autophagosomes in the risk zone of the preconditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
139
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 45 publications
5
139
1
4
Order By: Relevance
“…This suggests that the preconditioning effect of the lysosomal degradative pathways on maintenance of mitochondrial quality (as demonstrated by our data in Figs. 2G and 4G), 19 and perhaps on maintenance of ER homeostasis 63 plays a central role in shoring up cellular defenses to withstand the stress. 64 Indeed, we observe a reduction in prevalence of depolarized mitochondria in repetitively starved cardiomyocytes, in vitro (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the preconditioning effect of the lysosomal degradative pathways on maintenance of mitochondrial quality (as demonstrated by our data in Figs. 2G and 4G), 19 and perhaps on maintenance of ER homeostasis 63 plays a central role in shoring up cellular defenses to withstand the stress. 64 Indeed, we observe a reduction in prevalence of depolarized mitochondria in repetitively starved cardiomyocytes, in vitro (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of autophagy is also essential for cytoprotection during myocardial ischemia, 17 and pharmacologic stimulation of autophagy with rapamycin protects against postinfarction remodeling. 18 Myocardial autophagy is also induced with regimens of ischemic preconditioning; 19,20 and appears essential for the observed ischemic cytoprotection in ex-vivo ischemia-reperfusion injury. 19 Whether calorie restriction-induced autophagy confers ischemic cardioprotection is not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic preconditioning also induces autophagy to promote cardioprotective effects [15,16] . Housekeeping levels of autophagy are required for normal cardiac action; however, the autophagy response to stimuli is either an adaptive response or a detrimental effect [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is known to be activated during ischemic insult, but its contribution to neuronal death/survival is still being debated [16][17][18] . Recent reports also suggested an association between preconditioning and autophagy in both the heart and brain [19][20][21][22] . In an earlier study, we demonstrated that the neuroprotection induced by IPC is mediated by autophagy in a rat model of IPC, and the pharmacological induction of autophagy mimics the neuroprotection of IPC [23] .…”
Section: Introductionmentioning
confidence: 99%